ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA PENDIDIKAN MATEMATIKA DALAM PEMBELAJARAN MIKRO (Studi Kasus pada Mahasiswa Pendidikan Matematika FKIP UNS Tahun Akademik 2012/2013) - Frasetyana, Anita Diah; Sujadi, Imam; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research is to describe the basic teaching skills in microteaching of the students majoring in Mathematics Education of the Faculty of Teacher Training and Education of Sebelas Maret University in Academic Year 2012/2013. The subject of this research consisted of two students conducting a microteaching. One of the subject has high academic ability whereas the other subject has low academic abilityÂ  Type of the research was a qualitative case study research. The subjects of this research were taken by using the purposive sampling. The technique of analyzing the data was Miles and Huberman concept, namely, data reduction, data presentation, and conclusion drawing. The results of this research are as follows: the skill that the students have mastered in the apperception activity is the skill to conduct apperception by using the questions related to the learning material which is going to be learnt and giving description on the activity and/or scope of learning material of the class meeting; the skill that the students have mastered in asking questions to theirÂ  microteaching students is the skill to raise question clearly relevant to the problems discussed; the skill that the students have mastered in the reinforcement is the skill to use non-verbal reinforcement by nodding head and smiling; the skill that the students have mastered in conducting variation in teaching is the skill to vary the volume of voice and the standing position in the classroom; the skills that the students have mastered in explaining are the skills to present the learning material in structured or systematic sequence, to emphasize the important parts, to give examples by following deductive or inductive pattern, and to give feedback; the skill that the students have mastered in group activity is the skill to distribute the chance for their microteaching students to participate and to analyze or extend the view of their microteaching students; the skills that the students have mastered are the skills to give clear instruction and to get their microteaching students prepared by setting the size of the group and the number of the group members as well as to ask their microteaching students to account for their group activity; the skills that the students have mastered in the closing activity are the skills to make summary by either the students themselves and/or by involving their microteaching students and to conduct written test as an evaluation tool in teaching Mathematics.Keywords: basic teaching skill, microteaching, and teaching Mathematics.